Literacy of the countryside within the framework of the PNAIC: demands and challenges - Sidmar da Silva Oliveira; Obdália Santana Ferraz Silva; Úrsula Cunha Anecleto (Universidade Federal do Norte do Tocantins, 2019)
This study discusses the literacy of the countryside from formative propositions the National Pact for Literacy in the Right Age (PNAIC). The problem question that guides this research is: what are the implications the PNAIC for the countryside literacy? As a methodological process, based on the discursive textual analysis (Moraes & Galiazzi, 2016), we carried out a documentary research in the training books of the Program that deal with the rural education and held reflective sessions with literacy teachers. As a theoretical contribution, start with the discussions about continuing teacher education (Nóvoa, 1992; Imbernón, 2010); literacy (Kleiman, 1995; Tfouni, 2010); rural education (Caldart, 2002; 2011); among others. The study leads the understanding that continuing education may be relevant process when the collaborative reflection of teachers on the literacy practice in the daily school life, pointing out the need for literacy practices in rural schools connect to the reality of the students, overcoming discrepancy between the proposed and the realized. It is also inferred from the study that the PNAIC propositions need to establish a closer relationship with the literacy practices schools, that they approach the educational demands and specificities of the students and the community to which they belong.